The Bullying dan Mental Siswa: Peran Keluarga Dalam Pandangan Islam - Nelli Novyarni; Rimi Gusliana Mais; Imelda Aprileny; Maserih Maserih; Sumitro Sumitro (LPMP Imperium, 2021)
This activity aims to achieve the objectives of outreach activities for students (millennials) at Diponegoro School, Rawamangun, East Jakarta. as a community service program, this activity aims to provide an overview of how bullying and cyberbullying affect mental health, providing an overview of the negative impact of bullying behavior, and helping to encourage teenagers/students (millennial) to have good character and to help provide an image to teenagers/students (millennials) to be able to fortify themselves from the ease of getting negative information. The method used in this activity is counseling using zoom meetings by presenting speakers from religious experts. This activity can get a good response from the participants and the next activity can be planned. Keywords: Bullying, student mentality, family role, Islamic perspective